A day at the university fair: 'hot' brands, 'house of brands' and promotional tactics in higher education. Issue 2 (3rd July 2019) - Missaghian, Rod; Pizarro Milian, Roger
ABSTRACT: Research on promotional behavior within higher education has exploded over the last two decades, spurred on by the intensification of student recruitment. To date, studies have focused on mapping the content of conventional promotional texts (e.g. viewbooks, web sites), to identify how institutions depict themselves through them. By comparison, recruitment events, such as exhibitions or fairs, have received limited scholarly attention. This study aims to ameliorate this gap within the present literature, using observational methods and collaborative auto-ethnography to analyze branding strategies and broader social dynamics within a prominent Canadian university fair. Using such methods, this study identifies (i) variance in the uptake of 'house of brands' and 'branded house' strategies, (ii) diverging degrees of student interest across institutional types, along with (iii) 'niche'-oriented marketing tactics across information booths. Observed patterns are theorized from the standpoint of contemporary research within the field of organizational sociology and higher education marketing.